Clinical Characteristics, Risk Factors, and Outcomes of Patients with Polymicrobial Klebsiella pneumoniae Bloodstream Infections. (19th June 2021) - Song, Feizhen; Zhang, Kai; Huang, Jianjiang; Qian, Zhenhua; Zhou, Hongwei; Cai, Jiachang; Zheng, Cheng; Zhou, Feifei; Cui, Wei; Zhang, Gensheng
Abstract : Background . Polymicrobial Klebsiella pneumoniae bloodstream infection (KP-BSI) has been reported to account for more than 10% of all KP-BSI, but few studies have characterized polymicrobial KP-BSI. Our study investigated the clinical characteristics, risk factors, and outcomes of polymicrobial KP-BSI by comparing with monomicrobial KP-BSI. Methods . We conducted a single-center retrospective cohort study of patients with KP-BSI from 1 January 2013 to 31 December 2018 and collected the clinical data by reviewing electronic medical records. Results . Of the 818 patients with KP-BSI recruited, 13.9% (114/818) were polymicrobial KP-BSI. The severity of illness in polymicrobial and monomicrobial KP-BSI was similar, while the rate of resistance to carbapenems was obviously higher in polymicrobial KP-BSI (78.1% vs. 65.6%, p = 0.009 ). On multivariate analysis, hospitalization in burn ward (odds ratio (OR) 6.13, 95% confidence interval (CI) 2.00-18.76, p = 0.001 ) and intensive care unit (OR 2.39, 95% CI 1.05-5.43, p = 0.038 ) was independently associated with polymicrobial KP-BSI. Gram-negative bacteria accounted for the highest proportion (68.9%) among copathogens of polymicrobial KP-BSI, whereas gram-positive bacteria (22.9%) and Candida (8.2%) ranked the second and the third, respectively, with Acinetobacter baumannii being the most common (23.0%). Patients with polymicrobial KP-BSI had longer hospital days after BSI onset and total hospital days than patients with monomicrobial KP-BSI (median (interquartile range (IQR)), 19 (5, 39) vs. 12 (6, 25), 37 (21, 67) vs. 29 (16, 53), respectively, p < 0.05 ). The mortality did not differ between polymicrobial KP-BSI and monomicrobial KP-BSI (all p > 0.05 ). Conclusions . It was observed that polymicrobial KP-BSI accounted for a significant proportion among all KP-BSI in the current study. Hospitalization in burn ward and intensive care unit was an independent risk factor for the development of polymicrobial KP-BSI. The patients with polymicrobial KP-BSI had a higher rate of carbapenem-resistant K. pneumoniae and might have poor outcomes compared to monomicrobial KP-BSI.